2017
DOI: 10.1002/jms.4022
|View full text |Cite
|
Sign up to set email alerts
|

The main beam correction term in kinetic energy release from metastable peaks

Abstract: The correction term for the precursor ion signal width in determination of kinetic energy release is reviewed, and the correction term is formally derived. The derived correction term differs from the traditionally applied term. An experimental finding substantiates the inaccuracy in the latter. The application of the "T-value" to study kinetic energy release is found preferable to kinetic energy release distributions when the metastable peaks are slim and simple Gaussians. For electronically predissociated sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The experimental result processing methods have been thoroughly described in detail elsewhere. , The computational methods are outlined in section .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental result processing methods have been thoroughly described in detail elsewhere. , The computational methods are outlined in section .…”
Section: Resultsmentioning
confidence: 99%
“…Previously 5 we reported a factor 9 heavyatom 1°kinetic isotope effect (KIE) in the loss of a chlorine atom from CH 2 35 Cl 37 Cl + , a very low KER, and a massive H/D 2°KIE. In a recent publication, 6 applying a revised main beam correction term, we reported the KER for the loss of Cl from CH 2 35 Cl 2 + to be 30 μeV or borderline zero, presumably the lowest KER ever reported from a MIKE experiment. Other sources report KERs of 10−15 meV, 17−19 but these values are most likely incorrect due to an unrecognized contribution from CID. In our first report, 5 we also concluded that no metastable reaction was detectable for CD 2 Cl 2 + .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation